The underwater alphabet book - Pallotta, Jerry; Stewart, Edgar, 1959- (Watertown, Mass. : Charlesbridge, 1991)
From angelfish to zebra pipefish, this alphabet book depicts underwater creatures and scenes.
4.3
K-3
Keywords: Underwater exploration -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Underwater exploration; Alphabet; Underwater exploration; Alphabet